Underwater recording of electromyographic activity using fine-wire elektrodes - Okamoto, T.; Wolf, S. L. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The ftrst electromyographic (EMG) studies designed to analyze swimming motions in adults were performed by Ikai, Ishii, Miyashita (1964) using surface electrodes. Subsequently the technique was developed to analyze movement patterns in children and infants (Okamoto, 1976; Okamoto et al., 1976), still using surface electrodes. Most studies of aquatic movements in man have used amplification systems that are suspended out of the water some distance from the subject. As a result, investigators have had to contend with various technical problems, including movement artifact incurred by unstable leads between surface electrodes and recording equipment. It would seem that the provision for waterproof amp1illers, located close to the sight of pickup, could minimize such recording problems. Additionally, the use of indwelling electrodes could help to isolate activity from specillc muscles. In preparing to monitor underwater muscle performance for both swimming behavior in children and ambulation in rehabilitation patients we have developed an inexpensive, effective, and rapid method for recording EMG underwater using ftne-wire electrodes. Although ftne-wire electrodes have been used to record underwater activities in amphibians (Osse, 1969), to the best of our knowledge this clinical technique has not been reported previously. This paper describes our methodology and demonstrates its potential application.